2022
DOI: 10.3390/pr10102099
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Hydroquinone Coupled with Energy Generation through Microbial Fuel Cells Energized by Organic Waste

Abstract: Microbial fuel cell (MFC) technology has captured the scientific community’s attention in recent years owing to its ability to directly transform organic waste into electricity through electrochemical processes. Currently, MFC systems faces a number of barriers, with one of the most significant being the lack of organic substrate to provide enough energy for bacterial growth and activity. In the current work, rotten rice was utilized as an organic substrate to boost bacterial activity to produce more energy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…In addition, Nimje et al [58] reported that the power density of the Bacillus strains when used as a biocatalyst was 0.000105 mW/m 2 . However, a few investigations demonstrated that the found bacterial species (Figure 10) are well known as biodegradative and electroactive species, which we also found in our experiment [59,60].…”
Section: Bacterial Identificationsupporting
confidence: 86%
“…In addition, Nimje et al [58] reported that the power density of the Bacillus strains when used as a biocatalyst was 0.000105 mW/m 2 . However, a few investigations demonstrated that the found bacterial species (Figure 10) are well known as biodegradative and electroactive species, which we also found in our experiment [59,60].…”
Section: Bacterial Identificationsupporting
confidence: 86%
“…Several studies claim that the appearance of such structures on SEM indicates the presence of bacterial species. Although we observed other articles that followed the same pattern, this is just a hypothesis [57][58][59]. The anode biofilm was observed to possess the rod filament appendage's structure.…”
Section: Biological Characterizations Of Mfcmentioning
confidence: 67%
“…Although previous studies have shown that Pb 2+ and Hg 2+ levels of 50 to 200 mg/L are safe to treat, levels of more than 250 mg/L are a challenge for MFCs' systems [61]. We followed the same approach as other researchers and used EDX to analyze the biofilm [59,62]. It is obvious that EDX cannot provide information regarding metal ions.…”
Section: Biological Characterizations Of Mfcmentioning
confidence: 99%
“…For example, Van Der Velden et al ( 2022) calculated an internal resistance of 15.99 Ω in their MFCs using sediments from Saldanha Bay, which operated at pH 9 and used carbon electrodes [50]. In this same sense, Torlaema et al ( 2022) found an internal resistance of 38.87 Ω in their single-chamber MFCs, managing to generate voltage and current peaks of 168 mV and 0.168 mA using rice waste and graphite electrodes as a substrate [51]. Figure 4b shows the power density (PD) values in the current density (CD) of the MFCs, managing to show PDmax peaks of 475.32 ± 24.56 mW/cm 2 in CD of 5.539 A/cm 2 with a peak voltage of 1024.12 ± 25.16 mV.…”
Section: Results and Analysismentioning
confidence: 99%